Estimation of Price Volatility and the Convenience Yield - a Study Based on Zinc and Lead Example - Pera, Krystian; Saługa, Piotr (Określenie historycznej zmienności cen i premii z tytułu składowania dla cynku i ołowiu, 2010)
The volatility of prices is one of the most important parameters in the technical analysis of assets on the financial and commodity markets as well as the major indicator of interest for the investors. For mineral commodities, apart from price volatility, it is the convenience yield which plays a significant role. The two parameters are the key-variables used in forecasting commodity prices and real option pricing models. The paper makes an attempt to estimate historical volatility of prices and the convenience yield for zinc and lead relying upon data for years 2001-2008.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 114-130
Keywords: commodity futures market; zinc-and-lead industry; zinc and lead prices; price volatility; convenience yield